Serviço de Proteção e Atendimento Especializado a Famílias e Indivíduos (PAEFI): um espaço social para construção de autonomia? - Júnia Lúcia Pena de Andrade (2018)
This research aimed to clarify the social meaning of autonomy and actions that denote its construction between workers and users of the Service for Specialized Attention for Protection to Families and Individuals (PAEFI) in Belo Horizonte (BH)-MG. As for specific objectives, it proposes to analyze how the theme of autonomy appears in documents that orients the workers practices: the laws that structure SUAS and PAEFI; clarify the social meanings about autonomy that inspire the practice of PAEFIs workers; get to know the potentialities, difficulties and limitations in the intervention experiences for PAEFI workers that denote an autonomous aspect; investigate the relationship that former users, disconnected from PAEFI due to the overcoming of rights violations, establish between this overcoming and the workers follow-up process, searching for possible autonomy construction process between them. In Social Assistance (SA) and, especially in that orients PAEFI, the autonomy presents itself as an essential element to overcome the rights violation situation, as well as the citizenship exercise and the access to rights, main objectives of the service. The autonomy in Castoriadis present itself as the main theoretical referent of this research. Autonomy is the capacity of action and transformation of the subject in society, being it corollary of the wide concept of citizenship. The researchers implication, also worker in PAEFI, presented itself as a transversal element to the research. To the construction of the data in this social qualitative research, an option was made, initially for the reading of documents and referent that structure SA, having autonomy as focus. To approach the subjects, workers and users that have been disconnected from PAEFI due to the overcoming of the rights violation situation, we used strategies based in focal groups to instigate reflections in workers and get to know the meanings about the realized follow-up, besides semi-structured interviews with the former users. From the construction of the data, the categories were elaborated: a) meanings about PAEFI; b) meanings about the changes lived due to the follow-up of the former users with PAEFI; c) meanings workers have about autonomy and its construction in the relationship with the user. For the analyses, the triangulation was used between the autonomy conception(s) of SA, the social meanings of former users and professionals and the clarification of Castoriadis and some other authors about the theme. The autonomy in documents present itself as an element sine qua non for the subjects change, and, in a certain way, for the transformation of his/her context, what is closer to what Castoriadis brings to us. From the workers meanings, PAEFI presents itself as a potent space for the construction of autonomy. However, concomitantly, there is a tension when the service assumes the function to notify violations the organs in the system responsible, which can pass through the bond with the user and, consequently, the process of autonomys construction, in the service level. An emphasized meaning constructed is that the autonomy building is a process and inexhaustible. There is no unique, universal final product, as the overcome of the situation of rights violation that is desired institutionally. On the contrary, autonomy, built reflexively, presents itself as a process through small changes of the subject. For workers and for users, the importance of the self-valorization and multiply spaces that promote and strengthen interrogation is reinforced, base of the autonomy construction process